Contested borders: organized crime, governance, and bordering practices in Colombia-Venezuela borderlands - García Pinzón, Viviana (Trends in organized crime, 2021)
Based on the conceptualizations of organized crime as both an enterprise and a form of governance, borderland as a spatial category, and borders as institutions, this paper looks at the politics of bordering practices by organized crime in the Colombian-Venezuelan borderlands. It posits that contrary to the common assumptions about transnational organized crime, criminal organizations not only blur or erode the border but rather enforce it to their own benefit. In doing so, these groups set norms to regulate socio-spatial practices, informal and illegal economies, and migration flows, creating overlapping social orders and, lastly, (re)shaping the borderland. Theoretically, the analysis brings together insights from political geography, border studies, and organized crime literature, while empirically, it draws on direct observation, criminal justice data, and in-depth interviews.